Implementation of CORS GNSS and local geoid for precise orthometric height determination in land subsidence region (a case study in Semarang City) - Laode M Sabri (Jurnal Geospasial Indonesia, 2019)
Geoid has an important role in converting geodetic heights to physical heights, both in orthometric height system and normal height systems. At present, Semarang City already has gravimetric geoid with centimeter-level precision. This gravimetric was validated by geometric geoid measured by static method.  GNSS (Global Navigation Satellite System) measurement using static method needs long observation time and costly because it requires network that connect baselines and points. This study aims to implement CORS (Continous Operating Reference Station) GNSS in measuring geodetic height and to apply gravimetric geoid in orthometric height calculations. In this research, the gravimetric geoid recalculation process was carried out using gravity disturbance data of 2016. The geoid fitting process was carried out iteratively based on gravity data and modification of the integral of Hotine. Geodetic height measurements were carried out at 40 points distributed olong 50 km leveling network. Geodetic height measurements were refered to CORS GNSS of BIG (Geospatial Information Agency) and UNDIP (Diponegoro University) to produce standard deviation ranged from ±0.003 m to ±0.055. Geometric geoid checking with previous gravimetric geoid before fitting produced standard deviation of  ±0.037 m and  datum offset of -0.690 m. Geometric geoid checking for recent gravimetric geoid after fitting produces standard deviation of ±0.043 m and datum offset of -0.010 m. This study concluded that the refering geodetic coordinates to CORS stations by 1 hour observation of rapid static method and processing baselines in commercial software are sufficient for the determination of orthometric height in centimeter-level precision. This study also concluded that gravimetric geoid fitting based on gravity data shifting can minimize datum offset and shrinkage in geoid map.